2013
DOI: 10.5455/2320-6012.ijrms20130818
|View full text |Cite
|
Sign up to set email alerts
|

Single shot versus multiple shot antibiotic therapy in patients undergoing laparoscopic surgery: our experience

Abstract: The aim of our study was to see the effect of single dose regime versus multi dose regime of antibiotic in laparoscopic surgery; in terms of type of laparoscopic surgery done, type and dose of intravenous antibiotic given and the occurrence of post operative complications like wound gape, stitch abscess, local pain and discharge from the wound in both the groups. The present study was prospective, observational and longitudinal. Protocol of the procedure was formed along with Performa, Patient Information Shee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…The use of antibiotics in laparoscopic cholecystectomy is still arguable as some study still suggest that multiple doses of antibiotics have better outcome postoperatively. 15 In our study, the mean age of the patients was 37.37±14.3 years where 79(32%) were in the age group of 21 -30 years which was similar to the observation made by Shah YD et al 14 20 which concluded that there was no significant difference in outcome with SD or MD antibiotics use. Surgical site infection may occur even in clean surgery as numerous microbial factors play role in that.…”
Section: Discussionsupporting
confidence: 87%
“…The use of antibiotics in laparoscopic cholecystectomy is still arguable as some study still suggest that multiple doses of antibiotics have better outcome postoperatively. 15 In our study, the mean age of the patients was 37.37±14.3 years where 79(32%) were in the age group of 21 -30 years which was similar to the observation made by Shah YD et al 14 20 which concluded that there was no significant difference in outcome with SD or MD antibiotics use. Surgical site infection may occur even in clean surgery as numerous microbial factors play role in that.…”
Section: Discussionsupporting
confidence: 87%
“…17 Single dose of antibiotics emerged as equally effective, more cost-friendly, well tolerated and a preferred option as compared to multiple dose antibiotics in minimally invasive surgeries like laparoscopic cholesystecotmy. 18 Meijer et al 19 conducted a randomized, controlled, double-blind, multicenter trial, and they did not find any significant difference between the one-dose and multiple dose regimens in preventing post-operative wound infection. However, Waldvogel et al 20 have suggested that SSI may be found even in clean surgery as numerous microbial factors play a role, and antibiotic prophylaxis for not more than 24 hours is sufficient to prevent it as the critical period for the development of infection is short.…”
Section: Discussionmentioning
confidence: 99%